Genesis of pale microgranular masses in ophiolitic chromite deposits in northern Xinjiang: Analysis of the micro‐area composition of altered minerals using LA‐ICP‐MS. (13th January 2020) - Wang, Yu‐Wang; Xie, Hongjing; Guo, Boran; Shi, Yu; Zhou, Guochao
Abstract : The petrographic characteristics and micro‐area composition of altered minerals in pale microgranular masses (PMMs) that were discovered in the chromite mines of northern Xinjiang, China, were studied via laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS). There are six lithotypes of PMMs, namely, rodingitized vitrobasalt, gabbro‐diabase, ultramafite, tuff‐clastic rock, rodingite or skarn, and metasomatite. The texture, composition, and geochemical affinities of a series of altered minerals, such as clinopyroxenes, garnets, serpentines, and chlorites, show that the incompatible elements actively migrate with the Fe, Mg, alkali leaching losses, and Ca aggregates during the course of the alteration process. The geochemical characteristics of the major trace elements in the altered minerals are mostly influenced by the types of protoliths and minerals and have roughly inherited those properties from the protoliths. A marked difference exists between the serpentine geochemical characteristics of the major trace elements in the surrounding peridotites and the PMMs and/or metasomatite. This observation suggests that the two differences are derived from the altered protolith minerals instead of from the fluid metasomatism. Furthermore, the chlorite in the metasomatites inherits the properties of the chlorite component in the PMMs. This study examines the development of PMMs that might undergo two different mechanisms or (at least) two different periods of genesis, i.e., early ultramafic magma xenoliths and metasomatism, as indicated by the rock fabric, and late rodingitization, as indicated by the assemblage of altered minerals and the suite of geochemical affinities. The mechanism by which PMMs develop in peridotites reveals that some podiform chromite in this area may also be xenoliths that formed after chromite was captured by ultramafic magmas in early times.